The Outlines of Meaning’s Analysis of Social Phenomena in the Concept of S. L. Frank - Matveeva, Natalya (Slavica, 2018)
The present paper deals with the problem of how cultural meanings are perceived in S. L.Frank’s social theory. His conception lies between two main paths of sociological thought:Durkheim’s cognition of social facts as objective phenomena on the one hand, and Weber’scognition of subjective meanings of personal actions, on the other. In his theory Frank concentrateson the concept of objective forming idea-force, which resembles the concept ofsocial fact in its quality of exerting pressure on individual consciousness and volition, but itshould be brought into harmony with interpretive methodology. In Frank’s view social ideasare regarded as a force forming social relations and therefore lie in the foundation of socialinstitutions. These are, for example, ideas of state, of family, of friendship and so on. Socialideas are connected with the consciousness of the individual by their moral force. That iswhy such ideas are accepted by the individual at the emotional level of his spiritual life,because they believe that these ideas are true and organize their meanings and activities accordingto them. Thus social meanings of moral good or evil in human relations and in thesocial structure arise. At the same time they signify the emergence of sacred phenomena insociety. Human beings, according the Frank’s theory, have an internal need to be possessedby the sacred senses that give them the feeling of the participation in the implementation ofthe transcendent goals. Society is an objective living idea which provides sacred meaningsfor the individual. On the whole, a society’s life is formed by the historically specific complexof ideas that are freely accepted or rejected by individuals and determine their feelings andbehavior. There is no contradiction between personal freedom, creativity and social structurein S. Frank’s theory. The author of the present paperfinds similarities between S.Frank’s ideasand the fundamentals of cultural sociology.